Rational Fabrication of Nitrogen and Sulfur Codoped Carbon Nanotubes/MoS2 for High‐Performance Lithium–Sulfur Batteries. Issue 15 (27th June 2019) - Xiang, Kaixiong; Wen, Xiaoyu; Hu, Jun; Wang, Sicheng; Chen, Han
Abstract: Lithium–sulfur batteries are more promising and attractive than lithium‐ion batteries owing to a higher charge‐storage capacity. However, their commercial applications are hindered by an undesirable polysulfide shuttling effect during the cycling procedure. Herein, nitrogen and sulfur codoped carbon nanotubes intertwined with flower‐like molybdenum disulfide (NSCNTs/MoS2 ) were synthesized by using a feasible hydrothermal method and used as effective lithium polysulfides (LiPSs) tamers. The NSCNTs/MoS2 had a strong hybrid structure with strong interfacial interactions for physical confinement, chemical adsorption, and electrocatalytic conversion of intermediate LiPSs during the charge–discharge process. The NSCNTs intensified the flexibility and constructed a conductive framework for rapid ion/electron transfer, whereas the electrocatalysis of MoS2 managed the sulfur reaction chemistry in two ways: it chemically immobilized LiPSs through Li−S bonds and kinetically sped up the sulfur redox reactions. Owing to these merits, the Li–S cell with a NSCNTs/MoS2 host and NSCNTs/MoS2 ‐coated separator (NSCNTs/MoS2 /S‐NM) exhibited a high reversible capacity of 814 mAh g −1 at 1.0 C and long‐lasting cycling durability with an ultralow capacity decay of 0.02 % per cycle over 1000 cycles. Accordingly, rationally integrating the concepts of physical immobilization, chemical capture, and electrocatalysis to establish a multifaced cell structure for the architecture of high‐performance Li–S batteries is a significant strategy. Abstract : N, S codoped carbon nanotubes intertwined with flower‐like molybdenum disulfide (NSCNTs/MoS2 ) are synthesized by using a hydrothermal method. The NSCNTs/MoS2 reduce the formation of lithium polysulfides. The NSCNTs/MoS2 are used in Li–S battery cells, which exhibit a high reversible capacity of 814 mAh g −1 at 1.0 C and long cycling durability with an ultralow capacity decay of 0.02 % per cycle over 1000 cycles.